2011
DOI: 10.1159/000329932
|View full text |Cite
|
Sign up to set email alerts
|

<i>Interleukin-18</i> Promoter Polymorphism and Development of Antibodies to Surface Antigen of Hepatitis B Virus in Hemodialysis Patients

Abstract: Background: Interleukin (IL)-18 is involved in hepatitis B virus (HBV) clearance and augments antibodies against surface antigen of HBV (anti-HBsAg) production during DNA vaccination. The IL-18 –1297C>T (rs360719) polymorphism may modulate the IL-18 expression. Aim: To determine the potential association of IL-18 –1297C>T polymorphism with development of anti-HBsAg in hemodialysis (HD) patients. Methods: The frequency of IL-18 –1297C>T alleles and genotypes was identified by polymerase chain reaction restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…It has been shown that effective seroconversion after vaccination of HD patients depends on age, body mass, serum albumin concentration, type of dialyzer, duration of RRT, and underlying kidney disease [18,32-36]. Such risk factors of non-responsiveness as older age, shorter RRT duration and diabetic nephropathy were also present in the examined non-responders compared to responders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that effective seroconversion after vaccination of HD patients depends on age, body mass, serum albumin concentration, type of dialyzer, duration of RRT, and underlying kidney disease [18,32-36]. Such risk factors of non-responsiveness as older age, shorter RRT duration and diabetic nephropathy were also present in the examined non-responders compared to responders.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, IL genotypes ( IL10 IL-18 ) were associated with anti-HBs development in response to HBsAg in HD patients [18,39]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes encoding IL-18 (IL18 rs360719) and IL-12B p40 (IL12B rs321227) were linked to the development of anti-HBs in HD patients. 27, 28 On the other hand, the monocyte chemotactic protein 1 gene (MCP1-2518 A/G rs1024611) was not associated with anti-HBs formation in response to HBV vaccination, 29 although MCP1 is involved in Th2 polarization. 30 Secondly, our study was conducted in patients on RRT, who have impaired immune response.…”
Section: Massachusettsmentioning
confidence: 99%
“…Results of these studies indicate that in renal replacement therapy (RRT) subjects, there is a relatively weak association between polymorphisms of genes encoding Th cell cytokines and development of antibodies to surface antigen of hepatitis B virus (anti-HBs) in response to hepatitis B vaccination or hepatitis B virus (HBV) infection. [25][26][27][28][29][30] Active immunization against HBV may be less effective in ESRD patients due to vitamin D deficiency. 31 Vitamin D related genetic background may contribute to lower response to hepatitis B vaccination.…”
Section: Vaccination Against Hepatitis B Virusmentioning
confidence: 99%